From menace to marvel: An experimental study of tanned pufferfish leather from the invasive silver-cheeked toadfish () - Aylin Ulman; Muhammet Uzun; Alexandra Ioanid (Journal of Engineered Fibers and Fabrics)
This study assesses the feasibility of utilizing an invasive and inedible pufferfish species ( Lagocephalus sceleratus ) for non-food purposes, aiming to help control its population in the Mediterranean Sea. Previous research suggests that the skin of the pufferfish holds promise for yielding valuable and environmentally friendly exotic leather. We investigate various tanning methods to convert pufferfish skin into leather, providing the first comparative analysis of its kind. Our primary focus is to characterize the properties of this leather and offer essential insights for its utilization across different product categories. Industry-standard tests were conducted to assess the quality of the leather, which was then compared with conventional leather. We illustrate how such products can be developed through interdisciplinary collaborations. Our findings clearly demonstrate the high potential, quality, and feasibility of converting invasive pufferfish skin into leather and related products, thus opening avenues for its integration into the fashion industry. Furthermore, we showcase the creation of leather accessories and shoes to highlight potential applications, alongside an analysis of sewing and processing capabilities. In conclusion, this study meticulously presents a successful case study for managing one of the most severe marine invasive species in the Mediterranean Sea under a blue economy framework, while also introducing it as a new textile option for the fashion industry as a novel eco-friendly exotic fish leather alternative.